Curcumin-loaded core-shell biopolymer nanoparticles produced by the pH-driven method: Physicochemical and release properties. (1st September 2021) - Li, Zhenpeng; Lin, Quanquan; McClements, David Julian; Fu, Yuying; Xie, Hujun; Li, Teng; Chen, Guowen
Highlights: Alginate/NaCas-coated zein nanoparticles were prepared by a pH-driven method. Effects of the alginate/NaCas ratio on the structure of nanoparticles were studied. All the tested nanoparticles showed good stabilities under different environments. Higher ratios of alginate led to greater encapsulation efficiency of curcumin. Encapsulation of curcumin in nanoparticles prolonged its gastrointestinal release. Abstract: In this study, core-shell biopolymer nanoparticles were fabricated for the encapsulation and delivery of curcumin using a pH-driven method. The influences of the coating composition on the physicochemical properties and curcumin release characteristics of the core-shell nanoparticles were studied. Fourier transform infrared spectroscopy and X-ray diffraction analyses indicated that curcumin was encapsulated in an amorphous state inside the nanoparticles. Particle size and ζ-potential measurements indicated that the biopolymer nanoparticles were relatively stable under different environmental conditions: long term storage, heating, pH changes and salt. The DPPH radical scavenging activity of the curcumin was increased after encapsulation within the nanoparticles, whereas the gastrointestinal release of curcumin was prolonged. These results were attributed to the ability of alginate and NaCas to form a thick layer around the nanoparticles, which increased the steric and electrostatic repulsion between them, as well as inhibiting the release of curcumin.